The Influence Of Locus Of Control On Investment Decisions In The Economic Landscape - Kartika Dwi Pratiwi Siregar; Endang Supardi; Muhammad Arief Ramdhany (UNIVED Press, 2025)
This study explores the relationship between locus of control (LOC) and investment decisions in a dynamic economic landscape. Using a mixed-methods approach, this research examines how individuals' perceptions of control influence financial behavior. Quantitative surveys and qualitative interviews reveal that internal LOC correlates with proactive financial decision-making and effective risk management, whereas external LOC is associated with a more passive investment approach. These findings highlight the psychological mechanisms behind financial decision-making and provide implications for financial policy and education. By understanding how LOC impacts investment behavior, financial advisors and policymakers can develop targeted strategies to enhance financial literacy, resilience, and overall economic well-being.